Respuesta :

-4

Because 15x-7x= 8x
8x+5x= 13x
13x= -52
-52 / 13= -4
x = -4

First, condense what's on the right side of the problem:
[tex]15x-7x=-52-5x \\ 8x=-52-5x[/tex]
Nest, get all the terms with x on one side. To do this, add 5x to both sides:
[tex](8x)+5x=(-52-5x)+5x \\ 13x=-52[/tex]
Finally, divide each side by 13 to get x alone:
[tex](13x)/13=(-52)/13 \\ x=-4[/tex]
The answer is x = -4.

To check, simply plug -4 in for x like so:
[tex]15(-4)-7(-4)=-52-5(-4) \\ -60--28=-52--20 \\ -60+28=-52+20 \\ -32=-32[/tex]
Since we get the same answer on both sides of the equation, we know our answer is correct!

Hope this helps!